Gisi Marimas: Giat Literasi Dengan Makan Bergizi Dan Minum Yang Sehat Bersama Perpustakaan Cemerlang Desa Watualang - Hanifah Hikmawati (IAI Darussalam, 2023)
Abstract; This article discusses the importance of eating nutritious food and drinking healthy which is echoed by the Watualang Village Cemerlang Library to the community. Cemerlang Library is a library transformation based on social inclusion that focuses on community welfare and as a problem solver for phenomena that occur in society. One of the breakthroughs of social inclusion is the Cemerlang library of Watualang village in the form of the